Hygienism, salubrity and regulations. The Oporto's collective dwelling in the 1st half of the 20th century - Gisela Lameira (2012)
This article aim is to question the regulation's role in the collective housing production, not only in the design of the domestic space, but also in the transformation of the city's image and its morphological character at a specific historical period. The research framework proposes the concepts of "hygienism" and "salubrity" to support this aim and refers to the buildings that were conceived in Oporto between 1925 and 1957, and also to building and urban legislation applied in that period. There's a special interest in the housing's typological transformations and their urban morphological consequences. This recent and relatively unknown heritage is worthy of consideration as it engages deeply changes in Oporto's building tradition.